Aqueous zinc ion battery negative electrode material, preparation method and application thereof
ZnSe negative electrode material is prepared through hydrothermal synthesis and high-temperature selenization, and a modified slurry coating is formed on the surface of zinc foil, which solves the corrosion, dendrite and hydrogen evolution problems of zinc anode in aqueous zinc ion batteries, and improves the cycle life and Coulomb efficiency of the battery.
Patent Information
- Application Number
- CN202411852774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
The zinc negative electrode of aqueous zinc ion batteries is prone to metal corrosion, dendrite growth and hydrogen evolution side reactions, resulting in a decrease in battery cycle life, a decrease in Coulomb efficiency and a shortened battery life.
ZIF precursor was prepared by hydrothermal synthesis and was subjected to high-temperature selenization reaction with selenium powder to generate ZnSe negative electrode material. At the same time, a zinc negative electrode modification slurry is used to form a coating on the surface of the zinc foil to modify the negative electrode sheet to avoid direct contact between the electrolyte and the zinc foil.
It improves the conductivity of zinc ions, reduces the transfer resistance, inhibits dendrite growth and hydrogen evolution reaction, extends the cycle life of the battery, and improves the Coulomb efficiency and the overall performance of the battery.
Smart Images

Figure CN119673940A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemical energy storage devices, and particularly relates to an aqueous zinc ion battery negative electrode material, a preparation method and an application thereof. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) have attracted widespread attention from researchers due to their low cost, high safety, low toxicity, higher theoretical capacity and lower redox potential. They have become one of the ideal choices for large-scale electrochemical energy storage systems and are expected to become a substitute for lithium-ion batteries.
[0003] However, due to the unique aqueous electrolyte system, zinc metal still faces serious problems as a negative electrode, such as severe metal corrosion, dendrite growth, and side reactions such as hydrogen evolution. Tip effect is prone to occur during zinc nucleation, causing zinc to aggregate at the protrusions, thereby generating dendrites. As dendrites grow, they will not only pierce the diaphragm but also cause a short circuit in the battery. The continuous growth of zinc dendrites will lead to a reduction in battery cycle life, a decrease in coulomb efficiency, and the generation of dead zinc, which will reduce the battery life. The H2 produced in the hydrogen evolution reaction is the main cause of volume expansion and electrolyte leakage in aqueous zinc-ion batteries. A series of side reactions between the negative electrode and the electrolyte will also cause passivation of the zinc surface, endangering the electrochemical activity.
[0004] Therefore, the industrial application of zinc-based batteries urgently needs to develop zinc negative electrodes that can inhibit side reactions and dendrite growth on the negative electrode surface. Summary of the invention
[0005] In view of the above problems, the technical solutions adopted in this application are as follows: One aspect of the present application provides a method for preparing a negative electrode material for an aqueous zinc ion battery, comprising the following steps: (1) Dissolving a zinc metal salt and 2-methylimidazole in methanol respectively, and then adding the zinc metal salt methanol solution to the 2-methylimidazole methanol solution to obtain a mixed solution; subjecting the mixed solution to a hydrothermal synthesis reaction, cooling, washing, and drying to obtain a ZIF precursor; (2) mixing the ZIF precursor with selenium powder and performing a selenization reaction to obtain a selenized product; (3) grinding and mixing the powder of the selenide product and the binder, adding an organic solvent, mixing and stirring to obtain a zinc negative electrode modified slurry; (4) The zinc negative electrode modified slurry is coated on a zinc foil and dried to obtain a modified aqueous zinc ion battery negative electrode material.
[0006] In some examples, in step (2) of the above preparation method, the temperature of the selenization reaction is 900-1200°C, the heating rate is 5-10°C / min, the time of the selenization reaction is 8-10h; and the mass ratio of the ZIF precursor to the selenium powder is 1:1-5.
[0007] In some examples, in step (1) of the above preparation method, the mass ratio of the zinc-containing metal salt to 2-methylimidazole is 5-10:6-15; the temperature of the hydrothermal reaction is 100-150°C, and the time of the hydrothermal reaction is 4-6 hours; the zinc-containing metal salt includes one or more of ZnO, ZnSO4·7H2O, (CH3COO)2Zn·3H2O and Zn(NO3)2·6H2O.
[0008] In some examples, in step (1) of the preparation method above, before the hydrothermal synthesis reaction, the mixed solution is magnetically stirred at a speed of 500 to 700 r / min and a magnetic stirring time of 10 to 30 min; the number of washing times is 6 to 8 times; the drying temperature is 50 to 70 ° C and the drying time is 4 to 6 h.
[0009] In some examples, in step (3) of the above preparation method, the mass ratio of the powder of the selenized product to the binder is 7-9:1-3; The adhesive includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, and polyacrylic acid; the organic solvent includes one or more of N-methylpyrrolidone and deionized water; The ratio of the powder of the selenized product and the mixture of the grinded binder to the organic solvent is 100 mg: 300-500 μL.
[0010] In some examples, in step (3) of the above preparation method, the stirring speed is 200 to 450 r / min, and the stirring time is 4 to 10 h.
[0011] In some examples, in step (4) of the above preparation method, the drying temperature is 60-100° C., and the drying time is 4-8 hours.
[0012] Another aspect of the present application example provides an aqueous zinc ion battery negative electrode material, which is prepared according to the above preparation method.
[0013] In some aqueous zinc-ion battery negative electrode materials, a ZnSe aqueous zinc-ion battery negative electrode material is derived from a zeolite imidazolate framework material (ZIF-8) by selenization.
[0014] The third aspect of the present application provides an example of the application of the above aqueous zinc ion battery negative electrode material in an aqueous zinc ion battery.
[0015] The beneficial effects of this application are: 1. Due to the inherent poor conductivity of metal organic framework materials, the battery negative electrode sheet assembled by hydrothermally synthesized ZIF precursor has slow charge and discharge kinetics; the present application further designs a method of mixing the ZIF precursor with selenium powder and then calcining it at high temperature, so that the selenium powder is gasified at high temperature and reacts with Zn in the ZIF precursor. 2+ The ZIF precursor has large pores and a large specific surface area. The selenized product obtained by high-temperature selenization of the ZIF precursor retains the original morphology of the metal organic framework, so the resistance of the selenized product is smaller, which reduces the Zn 2+ The transfer resistance impedance is improved, and the conductivity is improved. Therefore, the aqueous zinc ion battery negative electrode sheet material obtained in this application promotes Zn 2+ Better stripping / plating helps avoid puncturing of the battery separator and causing short circuits, improving the coulombic efficiency and battery cycle performance.
[0016] 2. This application uses zinc negative electrode modified slurry to coat the surface of zinc foil to form a coating modification. The slurry coated on the surface of the negative electrode zinc foil can avoid direct contact between the electrolyte and the negative electrode zinc foil. 2+ Uniform plating and stripping between zinc foil and coated slurry layer, in Zn 2+ During the electroplating and stripping process from the electrolyte through the slurry layer to the zinc foil surface, the coating is desolvated and Zn 2+ The coating is separated from the bound water, and therefore has a certain barrier effect on the bound water. Therefore, the present application also inhibits the growth of dendrites, avoids the diaphragm being punctured and causing a short circuit, and improves the coulombic efficiency and the cycle performance of the battery.
[0017] 3. The raw materials (including zinc metal salts, such as zinc acetate, etc.) used in the preparation of the negative electrode materials for aqueous zinc ion batteries in this application are widely available, environmentally friendly, safe and pollution-free, have a simple preparation process, reduce costs, and have good application prospects for zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for describing the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 A is a scanning electron microscope (SEM) image of the ZIF-A-Se-1000 material in Example 2; Figure 1B , Figure 1C , Figure 1DThey are SEM images of ZIF-B-Se-1000, ZIF-C-Se-1000 and ZIF-D-Se-1000 materials in Comparative Example 2 respectively; Figure 2 is the X-ray diffraction pattern (XRD) of the ZIF-A-Se-1000 material and the ZIF-A material in Example 2; Figure 3 The stripping / electroplating cycle curves of the symmetrical battery assembled with the zinc electrode sheets in Example 2 and Comparative Example 1; Figure 4 The electrochemical impedance spectroscopy (EIS) curves of the symmetrical cells assembled with the zinc electrode sheets in Example 2 and Comparative Example 1; Figure 5 Linear sweep voltammetry (LSV) curves of Zn / / Cu half-cells assembled with zinc electrode sheets in Example 2 and Comparative Example 1; Figure 6 Cyclic voltammetry (CV) curves of the full batteries in Example 2 and Comparative Example 1; Figure 7 1 is the rate performance curve of the full battery in Example 2 and Comparative Example 1; Figure 8 The charge and discharge cycle curves and cycle efficiency curves of the full batteries in Example 2 and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0020] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0021] In the embodiment of the present application, a methanol solution containing zinc metal salt is added to a methanol solution of 2-methylimidazole to form a mixed solution, and the mixed solution is subjected to a hydrothermal synthesis reaction to prepare a ZIF-A precursor, and the ZIF-A precursor is then subjected to high-temperature selenization to obtain a selenized product ZIF-A-Se, and the zinc negative electrode modified slurry is prepared using the ZIF-A-Se powder, and the zinc negative electrode modified slurry is applied to the surface of the negative electrode zinc foil to construct a layer of artificial interface coating (the coating thickness is controlled at 20 to 25um), which overcomes the uneven electric field distribution caused by surface defects of the zinc foil (for example, unevenness, surface oxidation, etc.). The coating constructed in the embodiment of the present application helps to evenly distribute the charge at the interface between the electrode and the electrolyte, and avoids the formation of dendrites due to the tip effect caused by the aggregation of zinc ions at the surface defects of the zinc foil. In the embodiment of the present application, in the process of zinc ions being deposited on the surface of the zinc foil through the coating, the shuttling of zinc ions is affected by the coating and the electric field distribution is improved, which is beneficial to Zn2+ The migration and reaction kinetics of Zn-ion batteries can be accelerated to obtain a negative electrode material for aqueous zinc-ion batteries with better performance. In addition, the ZIF-A-Se coating formed by applying the zinc negative electrode modified slurry on the surface of zinc foil can change the Zn 2+ The deposition pattern of Zn 2+ Redistribute evenly and promote Zn 2+ Uniform nucleation and deposition reduce the polarization voltage of the battery, slow down the growth of zinc negative electrode surface dendrites, and improve the battery cycle performance. The preparation method of the modified aqueous zinc ion battery negative electrode material has simple steps, high repeatability, strong controllability of experimental conditions, and good universality of the experimental method.
[0022] Example 1 1. Preparation of negative electrode materials for aqueous zinc ion batteries 500 mL of CH3OH was measured and poured into a container, and 5.8 g of (CH3COO)2Zn·3H2O and 6.4 g of 2-methylimidazole were added to the CH3OH solution according to the mass ratio, respectively, and recorded as solution A and solution B, respectively. Solution A was gradually poured into solution B and magnetic stirring was performed. The magnetic stirring speed was 590 r / min and the stirring time was 10 min.
[0023] The stirred mixed solution was poured into a polytetrafluoroethylene liner, and the polytetrafluoroethylene liner was placed in a stainless steel autoclave for hydrothermal reaction. The hydrothermal time was 5 h and the temperature was set to 110°C.
[0024] After the reaction was completed, the mixture was naturally cooled to room temperature, and the precipitate obtained by the hydrothermal reaction was washed with deionized water and vacuum dried. After washing 6 times, a white precipitate was obtained, which was placed in a drying oven at 60°C and dried for 6 hours to obtain a Zn-based metal organic framework (Zn-MOF) precursor, which was recorded as ZIF-A.
[0025] The dried ZIF-A precursor was ground to obtain a powder (the particle size of the powder was in the micron level) and placed in a tube furnace for high-temperature selenization. The temperature of the tube furnace was 900°C during high-temperature selenization, the mass ratio of ZIF-A to selenium powder was 1:5, and the porcelain boat containing selenium powder was placed upstream of the tube furnace. The heating rate of the high-temperature selenization reaction at room temperature (25°C) was 8°C / min. When it reached 900°C, it was kept warm for 10 hours, and then naturally cooled to room temperature to obtain the selenized product ZIF-A-Se-900.
[0026] 180 mg of ZIF-A-Se-900 powder (particle size controlled at the micron level, for example, a particle size of 5 to 10 microns) and 20 mg of polyvinylidene fluoride (PVDF) were weighed, mixed and ground, and after grinding to achieve full mixing, an organic solvent N-methylpyrrolidone (NMP) was added, and the mixture was stirred at room temperature at a speed of 300 r / min for 4 hours to form a zinc negative electrode modified slurry.
[0027] The zinc negative electrode modified slurry is coated on the surface of the negative electrode zinc foil. The mixture of the above particle size powder and the organic solvent forms a viscous and uniform slurry, which is conducive to coating. After coating, it is vacuum dried at 60°C for 4 hours to form a uniform coating with a thickness of 20 to 25 um on the surface of the electrode. The modified aqueous zinc ion negative electrode material is prepared, which is recorded as ZIF-A-Se-900@Zn.
[0028] 2. Assemble symmetrical batteries The prepared modified aqueous zinc ion negative electrode plate material is cut into plates with a diameter of 12 mm by a slicer, and two plates with the same plate are selected to assemble a battery. A cut zinc negative electrode plate is placed in the positive electrode shell (the side without coating is in contact with the positive electrode shell), and then a glass fiber diaphragm is placed, and a pipette is used to drop 200uL of 2mol / L ZnSO4 as an electrolyte, and then another plate is placed on top of the diaphragm (the coated side contacts the diaphragm, and the side without coating material contacts the stainless steel gasket), and then the gasket and shrapnel are placed in turn, and finally the negative electrode shell is buckled, and the battery is packaged using a battery packaging machine to obtain a modified zinc negative electrode aqueous zinc ion symmetrical button battery, marked as ZIF-A-Se-900@Zn / / ZIF-A-Se-900@Zn / symmetrical button battery.
[0029] Example 2 1. Preparation of negative electrode materials for aqueous zinc ion batteries The hydrothermal synthesis, high-temperature selenization, modified slurry preparation and coating steps are the same as those in Example 1. In Example 2, the high-temperature selenization temperature is set to 1000° C. to obtain a modified aqueous zinc ion battery negative electrode material, which is recorded as ZIF-A-Se-1000@Zn.
[0030] 2. Assemble symmetrical batteries The assembly steps of the modified zinc negative electrode aqueous zinc ion symmetric button cell are the same as those in Example 1, and are marked as ZIF-A-Se-1000@Zn / / ZIF-A-Se-1000@Zn symmetric button cell.
[0031] Example 3 1. Preparation of negative electrode materials for aqueous zinc ion batteries The hydrothermal synthesis, high-temperature selenization, modified slurry preparation and coating steps are the same as those in Example 1. In Example 3, the high-temperature selenization temperature is set to 1200° C. to obtain a modified aqueous zinc ion battery negative electrode material, which is recorded as ZIF-A-Se-1200@Zn.
[0032] 2. Assemble symmetrical batteries The assembly steps of the modified zinc negative electrode aqueous zinc ion symmetric button cell are the same as those in Example 1, marked as ZIF-A-Se-1200@Zn / / ZIF-A-Se-1200@Zn / symmetric button cell.
[0033] Comparative Example 1 1. Preparation of negative electrode materials Cut the zinc foil into 2cm×2cm zinc sheets, soak the zinc sheets in dilute hydrochloric acid, and ultrasonicate for 5 minutes to remove the oxide film and impurities on the surface. The concentration of dilute hydrochloric acid is 0.1mol / L. Take out the ultrasonicated zinc sheets, wash them repeatedly with anhydrous ethanol and deionized water, and dry them in a natural environment. The purpose is to remove the oxide layer and surface impurities generated by the zinc foil in the air. The pretreated zinc sheets are used as zinc negative electrode materials.
[0034] 2. Assemble symmetrical batteries The pretreated zinc negative electrode material is cut into zinc negative electrode sheets with a diameter of 12 mm using a slicer, and two identical sheets are selected to assemble the battery. One of the sheets is placed in the positive electrode shell, a glass fiber diaphragm is placed, 200uL of 2mol / L ZnSO4 is dripped with a pipette as an electrolyte, and then another sheet is placed on top of the diaphragm. Then, the gasket and shrapnel are placed in sequence, and finally the negative electrode shell is buckled, and the battery is packaged using a battery packaging machine to obtain a zinc negative electrode aqueous zinc ion symmetrical button battery, marked as Zn / / Zn symmetrical button battery.
[0035] Comparative Example 2 1. Preparation of negative electrode materials for aqueous zinc ion batteries The steps of hydrothermal synthesis, high temperature selenization, preparation of modified slurry and coating are the same as those in Example 2. In Comparative Example 2, the zinc-containing metal salts used are ZnO, ZnSO4·7H2O, Zn(NO3) 2· 6H2O is used to synthesize a precursor, and the synthesized precursor is subjected to high-temperature selenization, and the selenization temperature is set to 1000°C to obtain a modified aqueous zinc ion battery negative electrode material. The modified aqueous zinc ion battery negative electrode materials corresponding to the above zinc metal salts are respectively recorded as ZIF-B-Se-1000@Zn, ZIF-C-Se-1000@Zn and ZIF-D-Se-1000@Zn.
[0036] 2. Assemble symmetrical batteries The assembly steps of the modified zinc negative electrode aqueous zinc ion symmetric button cell are the same as those in Example 1, which are respectively marked as modified symmetric button cell ZIF-B-Se-1000@Zn / / ZIF-B-Se-1000@Zn, modified symmetric button cell ZIF-C-Se-1000@Zn / / ZIF-C-Se-1000@Zn and modified zinc negative electrode aqueous zinc ion symmetric button cell ZIF-D-Se-1000@Zn / / ZIF-D-Se-1000@Zn.
[0037] Figure 1 A is a SEM image of the ZIF-A-Se-1000 material synthesized by (CH3COO)2Zn·3H2O. It can be seen that the material has uniform size, uniform size and uniform morphology of nanoparticles, which can provide a large specific surface area. In this embodiment 2, the specific surface area of the ZIF-A-Se-1000 material is between 100 and 145 m 2 / g, and the pore size distribution is concentrated in the range of 3.6 to 3.9 nm. Figure 1B , Figure 1C , Figure 1D The SEM images of ZIF materials synthesized from ZnO, ZnSO4, and Zn(NO3)2 after selenization at 1000°C (corresponding to ZIF-B-Se-1000, ZIF-C-Se-1000, and ZIF-D-Se-1000, respectively) show that after selenization at 1000°C, the three ZIF materials synthesized from zinc metal salts have uneven sizes and different morphologies; and the sizes of these three materials are relatively large, and even have block structures. These uneven shapes are difficult to form a uniform coating on the surface of the electrode through zinc negative electrode modification slurry after grinding to protect the zinc negative electrode. After the slurry of Example 2 is coated, the uniform coating formed inhibits the growth of dendrites, facilitates the desolvation of the coating, and Zn 2+ Separated from bound water, the coating also plays a certain role in blocking bound water, and the coating of this thickness does not affect the Zn 2+ Through the electrochemical reaction of the battery.
[0038] Figure 2 : These are the XRD characterization spectra of the precursor ZIF-A before high-temperature selenization sintering and ZIF-A-Se-1000 after high-temperature selenization sintering. The horizontal axis is the diffraction angle (2Theta), the vertical axis is the diffraction peak intensity (Intensity), and the standard card PDF#88-2345 corresponding to the phase structure. It can be seen from the figure that the obtained product is ZnSe, and the angle at 27.21° corresponds to the (1 1 1) crystal plane, 46.19° corresponds to the (2 0 0) crystal plane, and 53.56° corresponds to the (3 1 1) crystal plane; and, combined with the sharpness of the peaks in the characterization spectrum, the degree of crystallization of ZnSe in this embodiment is high.
[0039] Figure 3 The stripping / electroplating cycle curve of the symmetrical battery assembled with zinc electrode sheets in Example 2 and Comparative Example 1, the horizontal axis is time (Time), the vertical axis is voltage (Voltage), by -2 , surface capacity is 1 mAh cm -2 Under the test conditions, it can be seen that bare zinc (Bare Zn) exhibits a large polarization voltage (refer to the diagram, the polarization voltage is about 0.5V), and the battery short-circuits due to the growth of dendrites after 70 hours of circulation; while ZIF-A-Se-1000 can be stable for more than 400 hours and maintain a small polarization voltage (refer to the diagram, the polarization voltage is about 0.25V). Compared with the preparation method of the conventional negative electrode material in Comparative Example 1, the aqueous zinc ion battery negative electrode material prepared in Example 2 of the present application reduces the polarization voltage of the battery and improves the conductivity of the ZIF material, effectively solving the problem of the inherent poor conductivity of the ZIF organic compound leading to slow charge and discharge dynamics of the battery.
[0040] Figure 4 The electrochemical impedance spectroscopy (EIS) curves of the symmetrical batteries assembled in Example 2 and Comparative Example 1 are shown. Impedance is a vector, with the horizontal axis Z' being its real part and the vertical axis (Z") being its imaginary part. Figure 4 It can be seen that compared with the conventional negative electrode material in Comparative Example 1, the aqueous zinc ion battery negative electrode material prepared in Example 2 of the present application has a reduced Zn 2+ The transfer resistance of ions is smaller than that of ions, and a smaller transfer resistance can promote faster charge transfer and promote Zn 2+ ions on the zinc negative electrode. In addition, the applicant found that the temperature of high-temperature selenization has an effect on the deposition of Zn 2+ The influence of the impedance of the ion transfer resistance is more important. In Examples 1-3, the steps of preparing the ZIF precursor by hydrothermal synthesis, high-temperature selenization of the ZIF precursor, and preparation and coating of the modified slurry are the same, and only the temperature of the high-temperature selenization is changed. Figure 4 According to the EIS curve test results, the Zn 2+ The transfer resistance of ions. However, it should be emphasized that the temperature of high-temperature selenization is not something that can be obtained by those skilled in the art through limited experiments. The present application controls the high-temperature selenization temperature to be 900-1200°C. When the high-temperature selenization temperature is lower than 900°C, the degree of selenization is affected, and the precursor ZIF cannot be completely converted into ZnSe; when the high-temperature selenization temperature is higher than 1200°C, the material undergoes morphological changes, for example, structural collapse occurs. Therefore, the range of the selenization temperature affects the subsequent coating of the zinc negative electrode modified slurry, and then affects the morphology of the coating (for example, uniformity), and then affects the occurrence of side reactions such as dendrite growth of the zinc negative electrode.
[0041] Figure 5 Linear voltammetry (LSV) test was performed on the Zn / / Cu half-cell assembled with zinc electrode sheets to verify the inhibitory effect of ZIF-A-Se-1000 protective layer on hydrogen evolution reaction. Figure 5 It can be seen that at the same voltage, ZIF-A-Se-1000 / / Cu has a lower response current than Bare-Zn / / Cu. Therefore, by coating the surface of the metal zinc negative electrode, the occurrence of hydrogen evolution reaction is inhibited and the consumption of electrolyte by the battery during the cycle process is reduced.
[0042] Figure 6 The cyclic voltammetry test (CV, scanning rate of 0.5 mV / s) curves of the full battery in Example 2 and Comparative Example 1, the horizontal axis is voltage (Voltage, unit is V), and the vertical axis is current (Current, unit is mA); it can be seen that the two CV curves are basically the same in shape, both have obvious oxidation peaks and reduction peaks, and the modified electrode and the bare zinc electrode show similar redox curves, indicating that the introduced ZIF-A-Se-1000 protective layer, while playing a protective role, does not participate in the electrochemical reaction of charging and discharging in the battery, and therefore does not affect the electrochemical reaction of the battery.
[0043] Figure 7 The rate performance curves of the full battery in Example 2 and Comparative Example 1 show that the reversible specific capacity (Specific Capacity, unit: mAh / g) of ZIF-A-Se-1000 is higher than that of bare zinc under rate tests of the full battery under different current conditions, and ZIF-A-Se-1000 shows good rate performance. The horizontal axis corresponds to the cycle number.
[0044] Figure 8 The charge and discharge cycle curves and cycle efficiency curves of the full battery in Example 2 and Comparative Example 1 are shown. ZIF-A-Se-1000 and V2O5 are assembled into a ZIF-A-Se-1000@Zn / / V2O5 full battery for a long cycle test. It can be seen that after 1000 cycles (Cycle number, cycle number), ZIF-A-Se-1000 can still maintain a relatively high discharge specific capacity (Specific Capacity), the residual capacity is still higher than that of bare zinc, and the coulombic efficiency (coulombic efficiency, unit: %) remains stable, maintained at about 99%.
[0045] Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that it is still possible to modify the technical solutions described in the aforementioned embodiments, or to make equivalent replacements for some of the technical features therein; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a negative electrode material for an aqueous zinc ion battery, characterized in that: The preparation method comprises the following steps: (1) Dissolving a zinc metal salt and 2-methylimidazole in methanol respectively, and then adding the zinc metal salt methanol solution to the 2-methylimidazole methanol solution to obtain a mixed solution; subjecting the mixed solution to a hydrothermal synthesis reaction, cooling, washing, and drying to obtain a ZIF precursor; (2) mixing the ZIF precursor with selenium powder and performing a selenization reaction to obtain a selenized product; (3) grinding and mixing the powder of the selenide product and a binder, adding an organic solvent, mixing and stirring to obtain a zinc negative electrode modified slurry; (4) The zinc negative electrode modified slurry is coated on a zinc foil, and after drying, a modified aqueous zinc ion battery negative electrode material is obtained.
2. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the selenization reaction is 900-1200° C., the heating rate is 5-10° C. / min, and the time for the selenization reaction is 8-10 h; the mass ratio of the ZIF precursor to the selenium powder is 1:1-5.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the zinc-containing metal salt to 2-methylimidazole is 5-10:6-15; the temperature of the hydrothermal reaction is 100-150° C., and the time of the hydrothermal reaction is 4-6 hours; the zinc-containing metal salt includes one or more of ZnO, ZnSO4·7H2O, (CH3COO)2Zn·3H2O and Zn(NO3)2·6H2O.
4. The preparation method according to claim 3, characterized in that: In step (1), before the hydrothermal synthesis reaction, the mixed solution is magnetically stirred at a speed of 500 to 700 r / min and a magnetic stirring time of 10 to 30 min; the number of washing times is 6 to 8 times; the drying temperature is 50 to 70 ° C and the drying time is 4 to 6 h.
5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the powder of the selenized product to the binder is 7-9:1-3; The adhesive includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, and polyacrylic acid; the organic solvent includes one or more of N-methylpyrrolidone and deionized water; The ratio of the powder of the selenized product and the mixture of the grinded binder to the organic solvent is 100 mg: 300-500 μL.
6. The preparation method according to claim 5, characterized in that: In step (3), the stirring speed is 200 to 450 r / min, and the stirring time is 4 to 10 h.
7. The preparation method according to claim 1, characterized in that: In step (4), the drying temperature is 60 to 100° C. and the drying time is 4 to 8 hours.
8. A negative electrode material for an aqueous zinc ion battery obtained by the preparation method according to any one of claims 1 to 7.
9. The aqueous zinc ion battery negative electrode material according to claim 8, characterized in that: The aqueous zinc ion battery negative electrode material is an aqueous zinc ion battery negative electrode material derived from a zeolite imidazolate framework material by selenization.
10. Use of the negative electrode material for aqueous zinc ion batteries according to claim 8 or 9 in aqueous zinc ion batteries.